2020
DOI: 10.1002/acn3.51247
|View full text |Cite
|
Sign up to set email alerts
|

SUCLA2 Arg407Trp mutation can cause a nonprogressive movement disorder – deafness syndrome

Abstract: SUCLA2 is a component of mitochondrial succinate‐CoA ligase and nucleotide diphosphokinase activities. Its absence results in Krebs cycle failure, mitochondrial DNA depletion, and a childhood‐fatal encephalomyopathy. We describe a purely neurologic allelic form of the disease consisting of deafness, putamenal hyperintensity on MRI and a myoclonic‐dystonic movement disorder unchanging from childhood into, so far, the late fourth decade. We show that succinate supplementation circumvents the Krebs cycle block, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A previous study showed that IDH1 and IDH2 mRNA expression is notably reduced in the skin surrounding hidradenitis suppurativa lesions (56). Deletion of SUCLA2 leads to TCA circulatory failure, mitochondrial DNA depletion and fatal childhood encephalomyopathy (57). In addition, MDH2 silencing promotes ovarian cancer cell proliferation in vitro and in vivo (58).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that IDH1 and IDH2 mRNA expression is notably reduced in the skin surrounding hidradenitis suppurativa lesions (56). Deletion of SUCLA2 leads to TCA circulatory failure, mitochondrial DNA depletion and fatal childhood encephalomyopathy (57). In addition, MDH2 silencing promotes ovarian cancer cell proliferation in vitro and in vivo (58).…”
Section: Discussionmentioning
confidence: 99%
“…PCK1 is the first rate-limiting enzyme in liver gluconeogenesis and catalyzes the conversion of oxaloacetate to phosphoenolpyruvate; hypoxia can upregulate PCK1 to trigger gluconeogenesis to glycogenolysis [ 34 , 35 ]. SUCLA2 encodes the TCA cycle enzyme ADP-specific succinate-CoA ligase (β subunit) and is critical for mitochondrial succinate-CoA ligase and nucleotide diphosphokinase activities [ 36 ]. SUCLA2 can also regulate the succinylation and enzyme activity of glutaminase under oxidative stress, thereby enhancing the level of glutamine metabolism [ 37 ].…”
Section: Discussionmentioning
confidence: 99%